Površinska obdelava orodij za hladno oblikovanje - Legat, Franc (Kovine zlitine tehnologije, 1998)
The wear resiatance and the price of three different surface coatings: hard chromising, nitriding and TiN depozition is evaluated on the base of industrial tests of different toolings
Keywords: orodje; površinska obdelava; površinska zaščita; prevleke